Role of NFAT5 in the Immune System and Pathogenesis of Autoimmune Diseases - Lee, Naeun; Kim, Donghyun; Kim, Wan-Uk (Frontiers in Immunology, 2019)
The nuclear factor of activated T cells (NFAT5), also known as a tonicity-responsive enhancer-binding protein, was originally identified as a key transcription factor involved in maintaining cellular homeostasis against hypertonic and hyperosmotic environments. Although NFAT5 has been expressed and studied in various types of hyperosmolar tissues, evidence has emerged that NFAT5 plays a role in the development and activation of immune cells, especially T cells and macrophages. The immune-regulatory function of NFAT5 is achieved by inducing different target genes and different signaling pathways in both tonicity-dependent and -independent manners. Particularly in response to hyperosmotic stress, NFAT5 induces the generation of pathogenic TH17 cells and pro-inflammatory macrophages, contributing to autoimmune and inflammatory diseases. Meanwhile, with tonicity-independent stimuli, including activation of the Toll-like receptors and inflammatory cytokines, NFAT5 also can be activated and promotes immune cell survival, proliferation, migration, and angiogenesis. Moreover, under isotonic conditions, NFAT5 has been implicated in the pathogenesis of a variety of inflammatory and autoimmune diseases including rheumatoid arthritis. This review describes the current knowledge of NFAT5, focusing on its immune-regulatory functions, and it highlights the importance of NFAT5 as a novel therapeutic target for chronic inflammatory diseases.